Budownictwo kościelne w Królestwie Polskim - Jemielity, Witold (Prawo Kanoniczne, 1996)
The administrative regulations concerning the church erections should be divided into two groups = from the year 1817 and 1863. The first group was initiated with the provision of Alexander the First’s in 6/18.03.1817. Supplemented with the governor’s decision in 3.01.1818. The resolution of Alexander the First’s in 25.12.1823/6.01.1824, the regulations of the government, religion and public education board in 8.01.1829 and the decision of the governor’s in 8/20.10.1837. The latter group of regulations was introduced by Alexander the Second with the ucase dated from 8/20.01.1863. The Tsar’s order was supported by the Administrative Board of the Kingdom in 15/27.03.1863 and it sanctioned the instructions of church and other parish erections in 5/17.03.1863. Church administrations were allowed to spend 300 roubles. It was much more than the sum of the 7,50 roubles they had been allowed before. And the governors’ administrations had at their disposal 3000 roubles instead of 300, which had been available up till then. Decisions on church erections and renovations were made by Governor’s board which allowed to collect church money from a bank. The civil authorities, however decided if there was a need to build and renev churches, parishes, cementaries. They supervised the estate work and controled the expenses. The government also let set the oadside crosses, provate chapels and graves. The church authorities could only advise ahere and how to build until the end of the century, when they got a lot more influence. The Government Board in parishes was represented by church boards which consisted of a few civilians. After 1863 all parishioners voted for the obligatory subscriptions which became essential funds for the church building. Parish funds were reguralily replenisted by: collectors, fees for a grave place at a cementary, private donations and the fourth parts of parish administrators’ properties. In the first half of the century church erections were not conducted satisfactorily efficiently. The whole situation changed for better on the turn of the century. A great number of the brick churches, public chapels and presbyteries were built then.